2022
DOI: 10.21608/ejhm.2022.249509
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Thigh Circumference for the Prediction of Fetal Birth Weight using Ultrasound

Abstract: Background: Accurate foetal birth weight estimate is crucial for detecting growth limitation, preterm, and situations where clinical decisions affecting labour induction or delivery mode need to be made. This research study was conducted to determine the accuracy of predicting prenatal weight using foetal thigh circumference (TC). Patients and methods: Between November 2018 and September 2019, we performed a cross-sectional study of pregnant women. We included single intrauterine pregnant women with no complic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…This result is consistent with the results of the current study and agrees with it. The only different is that Ali et al (10) did not compare the thigh circumference result to results produced by the subcutaneous tissue thickness formula, Hadlock formula.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result is consistent with the results of the current study and agrees with it. The only different is that Ali et al (10) did not compare the thigh circumference result to results produced by the subcutaneous tissue thickness formula, Hadlock formula.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been conducted to find the correlation between thigh circumference and birth weight. In 2022, Ali et al [10] conducted a study to determine the accuracy of predicting prenatal weight using foetal thigh circumference. They enrolled 123 pregnant women and concluded that when used in conjunction with other fetal measures, the foetal thigh circumference may aid in the precise computation of fetal birth weight.…”
Section: Discussionmentioning
confidence: 99%